Enhancing abrasive wear resistance of IS-2062 steel in hydroturbine applications with WC-12 Co and WC-10 Co-4 Cr HVOF coatings - Harvinder Singh; Abhijit Bhowmik; Bharat Singh; Nitin Kumar; Virat Khanna; Kaushal Kumar; Gaurav Saini; Mohd Asif Shah (Scientific Reports)
Abstract Hydro-turbine components are frequently exposed to high-velocity abrasive and erosive environments, resulting in substantial wear. To overcome above challenge, this study investigates the mechanical performance of WC-12Co and WC-10Co-4Cr coatings applied to IS-2062 steel substrates using the High-Velocity Oxy-Fuel (HVOF) spraying technique. Following that the effectiveness of WC-12Co and WC-10Co-4Cr coatings in protecting steel substrates against degradation was evaluated. Microstructural analysis revealed that the powders possessed spherical morphologies with excellent flowability, enabling the formation of dense and uniform coatings. Microhardness tests showed a significant improvement, with hardness values increasing from 280 HV for uncoated steel to 1176 HV for WC-12Co and 1248 HV for WC-10Co-4Cr. Using FE-SEM images, the porosity analysis indicated that the lower porosity levels in WC-10Co-4Cr coatings, signifying superior coating integrity. Also, wear studies demonstrated a substantial reduction in wear rates and frictional forces for coated samples compared to the untreated substrate, with WC-10Co-4Cr providing the most favourable results. Results indicates that reported coating significantly enhance the durability of IS-2062 steel substrate with WC-10Co-4Cr coated surface shows better results than WC-12Co coated surface.